Curcumin against gastrointestinal cancer: A review of the pharmacological mechanisms underlying its antitumor activity - Fan, Yuanyuan; Zhang, Xiqin; Tong, Yuxin; Chen, Suning; Liang, Jingjing (Frontiers in Pharmacology, 2022)
Gastrointestinal cancer (GIC) poses a serious threat to human health globally. Curcumin (CUR), a hydrophobic polyphenol extracted from the rhizome of Curcuma longa, has shown reliable anticancer function and low toxicity, thereby offering broad research prospects. Numerous studies have demonstrated the pharmacological mechanisms underlying the effectiveness of CUR against GIC, including the induction of apoptosis and autophagy, arrest of the cell cycle, inhibition of the epithelial–mesenchymal transition(EMT) processes, inhibition of cell invasion and migration, regulation of multiple signaling pathways, sensitization to chemotherapy and reversal of resistance to such treatments, and regulation of the tumor survival environment. It has been confirmed that CUR exerts its antitumor effects on GIC through these mechanisms in vitro and in vivo. Moreover, treatment with CUR is safe and tolerable. Newly discovered types of regulated cell death(RCD), such as pyroptosis, necroptosis, and ferroptosis, may provide a new direction for research on the efficacy of CUR against GIC. In this review, we discuss the recently found pharmacological mechanisms underlying the effects of CUR against GIC (gastric and colorectal cancers). The objective is to provide a reference for further research on treatments against GIC.